The Importance of Turbulent Fluxes in the Surface Energy Balance of a Debris-Covered Glacier in the Himalayas - Steiner, Jakob F.; Litt, Maxime; Stigter, Emmy E.; Shea, Joseph; Bierkens, Marc F. P.; Immerzeel, Walter W. (Frontiers in Earth Science, 2018)
Surface energy balance models are common tools to estimate melt rates of debris-covered glaciers. In the Himalayas, radiative fluxes are occasionally measured, but very limited observations of turbulent fluxes on debris-covered tongues exist to date. We present measurements collected in autumn 2016 from the 26$^{th}$ of September to the 12$^{th}$ of October from an eddy correlation (EC) tower installed on the debris-covered Lirung Glacier in Nepal during the transition between monsoon and post-monsoon. Our observations suggest that surface energy losses through turbulent fluxes reduce the positive net radiative fluxes during daylight hours between 10 and 100%, and even lead to a net negative surface energy balance after noon. During clear days, turbulent flux losses increase to over 250 W m$^{-2}$ mainly due to high sensible heat fluxes. During overcast days the latent heat flux dominates the turbulent losses and together they reach just above 100 W m$^{-2}$. Subsequently, we validate the performance of three bulk approaches in reproducing the EC observations. Large differences exist between the approaches, and accurate estimates of surface temperature, wind speed, and surface roughness are necessary for their performance to be reasonable. Moreover, the tested bulk approaches generally overestimate turbulent latent heat fluxes by a factor 3 on clear days, because the debris-covered surface dries out rapidly, while the bulk equations assume surface saturation. Improvements to bulk surface energy models should therefore include the drying process of the surface. A sensitivity analysis suggests that, in order to be useful in distributed melt models, an accurate extrapolation of wind speed, surface temperature and surface roughness in space is a prerequisite. \textcolor{red}{By applying the best performing bulk model over a complete melt period, we show that turbulent fluxes to reduce the available energy for melt at the debris surface by 17$%$ even at very low wind speeds.} Overall, we conclude that turbulent fluxes play an essential role in the surface energy balance of debris-covered glaciers and that it is essential to include them in melt models.